Reflections of the Distance Education Process on Higher Education: A Probability Course Example - Çiğdem İnci Kuzu (Journal of Educational Issues, 2024)
Evaluating the effects of the Coronavirus (Covid-19) pandemic on distance education applications in higher education is important for future practice. In this context, the aim of the study is to determine preservice mathematics teachers’ conceptual-procedural knowledge level competencies and general thoughts about distance education in the distance education probability course in the department of mathematics teaching. In the study, a questionnaire consisting of 18 questions was prepared in the light of the literature as a data collection tool for 52 preservice mathematics teachers who took the probability course with distance education in the 2020-2021 academic year. After the implementations, one-to-one interviews were made with the lecturer conducting the course. The data of the study were analysed with the descriptive analysis method. As a result, it was determined that the conceptual-operative knowledge of the preservice mathematics teachers in the probability course in the distance education process was at a medium level. Although it was determined that the participation in online lessons was quite low compared to the lessons taught face-to-face, the preservice teachers mostly followed the lessons from asynchronous recordings, but there was no low performance or unwillingness in the preservice teachers who attended the lessons online. It has been determined that the biggest problem with distance education is the internet access and the low reliability of evaluation process. To increase the reliability, it has been determined that the transition to camera-controlled exams and the use of the safe exam browser (SEB) have been introduced.